Relationships Between Reading for Pleasure and Children’s Wellbeing in Aotearoa New Zealand - Boyask, Ruth; Milne, John; Jackson, Jayne; May, Robyn; Blokker, Sabine (Ministry of Social Development, New Zealand, 2024)
This study considers how experiences of reading for pleasure and wellbeing may affect one another, especially whether experiences of reading throughout the life course enhance wellbeing. Associations are examined between reading affect, or how children felt about and engaged with reading prior to, during and after the COVID-19 pandemic, with how they experienced wellbeing in their COVID-19 bubbles and since. The study draws upon GUiNZ data and focus groups with children at a similar age to the GUiNZ cohort. Positive wellbeing outcomes associated with affective experiences of reading are identified.